Interaction of Lithuanian and Belarusian Dialects in the Surroundings of Radun - Tuomienė, Nijolė (Respectus Philologicus, 2021)
The research focuses on the interaction of the Lithuanian and Belarusian languages in thesurroundings of Radun (Belarus, Voranava district, Lith. Rodūnia). Employing the language changemethodology, the paper presents a detailed analysis of the most prominent cases of phonetic interference oftwo – old and middle – generations of residents in both languages spoken by them.The data show that the oldest residents are expressing both languages using the Lithuanian articulatory base. Over time, the characteristic Lithuanian features begin to level: varies the pronunciation of a; in open endings, the long tense vowels i, ы are usually pronounced as é; unstressed vowels are reduced inconsistently, etc.As Lithuanian is for the middle-generation speakers, it already demonstrates essential changes, whichoccurred because they started expressing their Lithuanian using the Belarusian articulatory base. First of all, they usually lengthen stressed short vowels; they do no longer pronounce unstressed long vowels; they donot distinguish between acute – or circumflex-accented mixed i, u + R type diphthongs; the distinction between the falling and rising diphthongs ai, au, is made based on phonetic, not accentual, factors; the palatalised dental consonants t, d are replaced by the palatalised velar consonants k, g.
Keywords: language contact; border region dialects; Southern Aukštaitian; Belarusian dialect; bilingualism; phonetic interference